2020
DOI: 10.1186/s13046-020-01756-y
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Chemoattractant Protein-1 promotes cancer cell migration via c-Raf/MAPK/AP-1 pathway and MMP-9 production in osteosarcoma

Abstract: Background Osteosarcoma is generally reported among younger individuals and has a very poor prognosis, particularly for the development of metastasis. However, more effective metastatic biomarkers and therapeutic methods are absent. Monocyte chemoattractant protein-1 (MCP-1) is involved in cancer progression and inflammatory recruitment. Although previous studies have reported higher serum MCP-1 levels in patients with osteosarcoma, the role of MCP-1 in osteosarcoma progression remains to be ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 59 publications
0
23
0
Order By: Relevance
“…In osteosarcoma, Chen et al, reported that c-Met Inhibitor suppresses osteosarcoma progression via the ERK1/2 pathway [ 34 ]. In addition, Liu et al demonstrated that monocyte chemoattractant protein-1 regulates cell mobility via ERK/AP-1 pathway in osteosarcoma cells [ 35 ]. However, inhibiting ERK pathway could imply that other processes may be repressed.…”
Section: Discussionmentioning
confidence: 99%
“…In osteosarcoma, Chen et al, reported that c-Met Inhibitor suppresses osteosarcoma progression via the ERK1/2 pathway [ 34 ]. In addition, Liu et al demonstrated that monocyte chemoattractant protein-1 regulates cell mobility via ERK/AP-1 pathway in osteosarcoma cells [ 35 ]. However, inhibiting ERK pathway could imply that other processes may be repressed.…”
Section: Discussionmentioning
confidence: 99%
“…The literature data also show that there is an increased risk of developing GC after gastric surgery [ 55 ]. The time lag between initial gastric surgery for mild disease and the development of gastric stump cancer is around 30 years or more, compared with 12 years if surgery was performed due to earlier detection of GC lesions [ 56 ].…”
Section: Gastric Cancer—risk Factors Symptoms and Classificationmentioning
confidence: 99%
“…MCP-1 also induces Akt activation in a dose-dependent manner (46). In addition to the activation of the PI3K/Akt/mTOR signaling pathway, the c-Raf/MEK/ERK and MAPK signaling pathways play a role in MCP-1-induced tumor migration (47). Furthermore, the IP3-dependent Akt/PKB signaling pathway is associated with MCP-1-induced tumor proliferation and migration (48).…”
Section: Mcp-1 Acts On Cancer Cells Directlymentioning
confidence: 99%
“…MCP-1 enhances the aggressiveness of NSCLC cells by increasing the level of MMP-9 expression in vitro (50). MCP-1 induces MMP production by activating the ERK1/2 and p38 MAPK signaling pathways, and upregulates MMP by activating c-Raf/Raf-1, MEK, ERK, MAPK, c-Jun, NF-κB and AP-1 (47,51,52). MMP cleaves cell-to-cell and cell-extracellular matrix adhesion components, which promotes cell detachment and leads to epithelial-mesenchymal transition (EMT) and enhances metastasis (53).…”
Section: Mcp-1 Acts On Cancer Cells Directlymentioning
confidence: 99%